Tumor cells escape immunosurveillance by hampering LFA-1 - Upadhyay, Shishir; Murugu, Lewis; Svensson, Lena (Frontiers in Immunology, 2025)
During tumor immunosurveillance, leukocytes play a crucial role in the cellular defense system, working collaboratively with other immune components to recognize and eliminate aberrant cells. Integral to this process is the integrin Lymphocyte Function-Associated Antigen 1 (LFA-1). LFA-1 facilitates adhesion during leukocyte migration and helps establish stable cell-to-cell contacts between leukocytes and their targets. Additionally, as a receptor, LFA-1 signaling activates leukocytes, promoting their differentiation and effector functions against cancer. However, tumors can develop mechanisms to evade immune clearance by disrupting LFA-1 functions or hijacking its pathways. In this review, we first detail how leukocytes utilize LFA-1 during immunosurveillance and then explore how tumors counteract this process in the tumor microenvironment (TME) by either altering LFA-1 functions or exploiting it to drive tumorigenesis. Moreover, we discuss therapeutic strategies targeting LFA-1, including inhibitors tested in laboratory studies and animal models, highlighting their potential as anticancer interventions and the need for further research to evaluate their clinical utility.